Evaluating Crime and Traffic Violation Management through Safe City Cameras: A Case Study of Multan under the Punjab Safe Cities Authority - Fatima; Ramna Bashir; Wajeeha Shahid; Azka Tajamal; Noman Nadeem; Dr. Ahmad Saad (ACADEMIA International Journal for Social Sciences, 2025)
Traffic violations pose a serious challenge to urban governance and public safety in Pakistan. The introduction of surveillance-based traffic management systems by the Punjab Safe Cities Authority (PSCA) aims to enhance deterrence, improve compliance, and reduce road accidents. This study evaluates traffic violation trends in Multan before and after the implementation of surveillance infrastructure, comparing data from 2024 (pre-surveillance) and 2025 (post-surveillance). Using a quantitative research design and secondary data analysis, the study examines changes in overall violations and specific categories such as signal jumping, over-speeding, and helmet/seatbelt non-compliance. Statistical analysis reveals a significant reduction in traffic violations after surveillance implementation, supporting deterrence theory. The findings highlight the effectiveness of automated enforcement and provide policy-relevant insights for urban traffic management in Punjab.